Adsorption and molecular weight fractionation of dissolved organic matters with different origins on colloidal surface. (December 2020) - Pan, Jizheng; Fu, Xiaowei; Wang, Changhui; Song, Na; Lv, Xizhi; Xu, Huacheng
Abstract: Dissolved organic matter (DOM) adsorption on colloid surface occurred ubiquitously in aquatic ecosystems, while variations in molecular weight (MW) distribution during adsorption remained poorly understood. In this study, the adsorption and MW fractionation of aquatic DOMs with different origins (e.g., macrophyte- and algae-derived, MDOM and ADOM, respectively) on colloid surface were examined using total organic carbon, absorption and fluorescence spectroscopy, and flow field flow fractionation (FlFFF) analysis. Both the total organic carbon and spectroscopic results showed the predominant adsorption of DOMs within the first 45 min, which behaved not synchronously with MW fractionation. Quantitative FlFFF analysis further indicated that the organic ligands with different MWs exhibited different adsorption affinities on colloid surface. It was found that 5–15 kDa and 50 kDã0.45 μm were preferential adsorption fraction for humic- and protein-like MDOM, respectively, while 0.3–2 kDa and 0.3–50 kDa were preferential adsorption fraction for humic- and protein-like ADOM, respectively. Therefore, the MW fractionation of DOMs upon adsorption was highly dependent on DOM origins as well as specific components. Results obtained herein can enlarge our insights into adsorption and the resultant behavior and fate of DOMs that were highly related with the MW fractionation in aquatic environments. Graphical abstract: Image 1 Highlights: Adsorption and MW fractionation of MDOM and ADOM on colloid surface were studied. MW fractionation occurred later than adsorption process. 5–15 kDa and 50 kDã0.45 μm were preferential adsorption fraction for humic- and protein-like MDOM, respectively. 0.3–2 kDa and 0.3–50 kDa were preferential adsorption fraction for humic- and protein-like ADOM, respectively. MW fractionation during adsorption was related to DOM origins and organic components.